Il trovatore Blacasset: Edizione critica a cura di Barbara Francioni. Premessa di Riccardo Viel (Carte Romanze, 2024)
The troubadour Blacasset (first half of the 13th century) can be considered as one of the last representatives of the declining Occitan aristocracy, still loyal to the knightly codes of valour that were increasingly losing their edge at the time. The volume presents a biographical, historical, philological and ecdotic study of the surviving works of the troubadour, with a final glossary and a general study on the manuscript tradition.
Keywords: troubadours; Blacasset; Blacatz; Occitan poetry; glossary; manuscript tradition